Statistical Optimization of Process Variables for BiodieselProduction from Lagenaria Siceraria Seed Oil (International Journal of Integrative Research (IJIR), 2024)
Rising energy demand has led to progressive increase in thecost of fossil fuel globally. The exploration and exploitationof fossil fuel has led to depletion of oil reserves, moreoverthese fossil fuels are not only expensive but also has severeenvironmental consequences. Renewable and sustainableenergy resources gained greater importance in the currentsituation to supplement and minimize the environmentalpollution load and to compensate the energy demandworldwide. Biodiesel can be produced from myriad sourcessuch as waste or virgin oil, algae, and animal fats.Optimization of process variables to produce biodieselproves to be economic and effective way of producingbiodiesel. In this study RSM based optimization was carriedout using five-level, four-factorial central composite designin thirty (30) runs. Design expert version 6.0 was used for thestudy. The four processing variables under study are A:catalyst concentration, B: methanol to oil molar ratio, C:reaction time and D: temperature. The optimum conditionsfor maximum biodiesel (88.40%) was; methanol to oil molarratio (9.07:1), reaction time (70.59min), reaction temperature(53.090C), and amount of catalyst (0.88). The regressionequation obtained for the model having a coefficient ofcorrelation (R2), and adjusted coefficient of correlation(R2adj) are “Pred R-Squared" of 0.927 is in reasonableagreement with the "Adj R-Squared" of 0.911. "AdeqPrecision" measures the signal to noise ratio. A ratio greaterthan 4 is desirable. Ratio of 13.200 reported for this workindicates an adequate signal
Keywords: Biodiesel, Oil, Renewable, Temperature